Pengaruh penerapan problem based learning terhadap literasi lingkungan siswa SMP pada materi pencemaran lingkungan - Siddiq, Muhamad Nur; Supriatno, Bambang; Saefudin, Saefudin (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
This study was aimed to investigate the effect of problem based learning to environmental literacy for junior high school in environmental pollution subject. The study of students’ environmental literacy covered three aspects, there were knowledge, attitudes, and cognitive skills. The research methods used quasi-experimental and non-equivalent control group design. The sample of this research was seventh grade students in junior high school consisting of 27 experimental class students and 25 control class students. The instruments used in this study were multiple choice questions for aspects of knowledge and cognitive skills with Jatigede Reservoir as an environmental content, Likert scale questionnaires for attitude aspects, observation sheets of problem based learning syntax and student questionnaire in learning problem based learning. Pre test was given to the experimental and control class before learning begun and post test was given to the experimental and control class after the last learning was held. The results showed that the knowledge aspect showed a significant difference which meant that there was an influence from the results of the treatment given, while the aspect of cognitive attitude and skills did not show a significant difference, which meant there was no influence from the results of the treatment given. The achievement of the syntax of problem based learning is in the category of almost all activities. Students’ responses to the implementation of problem based learning showed an agreed response.